2023
DOI: 10.3847/1538-4357/aca7ba
|View full text |Cite
|
Sign up to set email alerts
|

The Binary and the Disk: The Beauty is Found within NGC3132 with JWST

Abstract: The planetary nebula (PN) NGC 3132 is a striking example of the dramatic but poorly understood mass-loss phenomena that (1–8) M ⊙ stars undergo during their death throes as they evolve into white dwarfs (WDs). From an analysis of JWST multiwavelength (0.9–18 μm) imaging of NGC 3132, we report the discovery of an extended dust cloud around the WD central star (CS) of NGC 3132, seen most prominently in the 18 μm image, with a surface-brightness-limited radial extent of ≳2″. We show that the A2V… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The presence of such intermittent, wobbling (possibly precessing) jets would strongly suggest that the mass-losing progenitor was a member of an interacting triple (as opposed to double) star system (De Marco et al 2022, and references therein). As detailed in De Marco et al (2022), the likelihood that the mass-losing AGB progenitor was a member of a hierarchical multiple system 11 is further supported by JWST's detection of both a thermal IR excess from a dust disk at the central star (see also Sahai et al 2023) and a ring or spiral pattern in the nebula's extensive H 2 halo.…”
Section: Implications For the Shaping Of Ngc 3132 By Its Central Star...mentioning
confidence: 87%
See 1 more Smart Citation
“…The presence of such intermittent, wobbling (possibly precessing) jets would strongly suggest that the mass-losing progenitor was a member of an interacting triple (as opposed to double) star system (De Marco et al 2022, and references therein). As detailed in De Marco et al (2022), the likelihood that the mass-losing AGB progenitor was a member of a hierarchical multiple system 11 is further supported by JWST's detection of both a thermal IR excess from a dust disk at the central star (see also Sahai et al 2023) and a ring or spiral pattern in the nebula's extensive H 2 halo.…”
Section: Implications For the Shaping Of Ngc 3132 By Its Central Star...mentioning
confidence: 87%
“…De Marco et al (2022) assert that these structures were most likely sculpted by an unseen companion or companions orbiting within ∼60 au of the PN progenitor. Furthermore, the JWST Mid-IR Instrument images demonstrate the ultra-hot central star has a significant IR excess that most likely emanates from a dusty disk that formed as the result of a close binary interaction, albeit not necessarily with the same companion that generated the H 2 ring and arc systems (De Marco et al 2022;Sahai et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Other gravitational paradigms are still being developed in the literature. An increasingly common one is that the orientation and kinetic energies of the flow pattern are influenced by multiple nearby companions and/or their related accretion flows, as invoked recently by De Marco et al (2022) and Sahai et al (2023) to explain the morphology of NGC 3132, and by Henney et al (2021) to account for orientations and ages of five ejection events over the past ∼3500 yr in NGC 6210. For similar reasons, K+22a suggested that stellar multiplicity is highly likely in NGC 6302 (K+22a).…”
Section: Formation and Ejection Paradigmsmentioning
confidence: 99%